Scoping Review: Metabolite and Pharmacological Activities in Lontar Fruit (Borassus flabellifer Linn.) - Tince Bety Amarduan; Yulia Sari; Brian Wasita (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
The development of medicine depends heavily on medicinal plants. They include variousphytochemicals that can have physiological effects on people. Among them is the Borassus flabellifer Linn., also known as the lontar plant, which is a tropical plant in the Araceae family and is recognized for its medicinal qualities in traditional medicine. It is also referred to as the Palmyra palm. This study aims to gather information on the phytochemical compounds and pharmacological activities of palm fruit using a literature review. The literature search was conducted online using appropriate keywords and included both international and national indexed databases, covering the last 10 years (2014 - 2024). Tannins, saponins, glycosides, alkaloids, terpenoids, albuminoids, anthracene, betulinic acid, carotenoids, flavonoids, free anthraquinones, glucomannan, gums, lupeol, phlobatannin, phenols, quercetin, phytosterols, triterpenoids, quinones, cardiac glycosides, steroids, coumarins, and betacyanin have been identified as chemical components in palm fruit based on the 19 studies that were gathered. The pharmacological activities of palm fruit include antibacterial, antidiabetic, antihyperlipidemic, antihyperglycemic, antioxidant, and anticancer.